Meldonium: drug which brought disrepute to sport - Meher, Bikash Ranjan; Das, Smita; Mohanty, Rashmi Ranjan (International Journal of Basic & Clinical Pharmacology, 2017)
World of sports have been rocked by doping scandals every now and then and World Anti-Doping Agency(WADA) has banned several offending drugs at different times to counter this menace. Meldonium is the recent addition to the long list of drugs banned by WADA to prevent its misuse among the athletes. Meldonium is a carnitine synthesis inhibitor and has been approved by some European countries for the management of cardiac diseases like angina pectoris and congestive cardiac failure. Apart from these, it has numerous other indications like bronchial asthma, bronchitis and retinopathies. It had also been used by athletes across the world because of its presumptive role in increasing the performance.